Vascular Redistribution for SIRT—A Quantitative Assessment of Treatment Success and Long-Term Analysis of Recurrence and Survival Outcomes - Borg, Philip; Wong, Jen Jou; Lawrance, Nicholas; Chander, Amarjot; Tipping, Jill; Bell, Jon; Mullan, Damian; Manoharan, Prakash; Jeans, Steve; Lawrance, Jeremy (Journal of Clinical Interventional Radiology ISVIR, 2019)
Aim Flow redistribution is not uncommonly performed as a treatment strategy to optimize delivery of radioembolization particles to the liver. We quantitatively evaluated the effect of vessel embolization to promote flow redistribution when performing selective internal radiation therapy (SIRT) for liver metastases, and assessed long-term outcomes of treatment.Materials and Methods One hundred and fifty-eight SIRT procedures over an 8-year period were retrospectively reviewed. Twenty-three patients who underwent partial/whole embolization of the left hepatic artery were compared to a control group of 18 patients who did not receive any hepatic embolization as part of their work up. Counts were measured for each patient on both the post-99mTcMAA injection, and the post-90Y microspheres injection imaging. Recurrence and survival rates were also measured.Results A statistically significant shift in the right:left ratio between planning and treatment procedures was seen in patients who had vessel embolization in favor of the embolized lobe (p = 0.014). There was no significant difference in the time to recurrence in the embolized lobes versus the nonembolized lobes. No significant difference in overall survival was detected between the two cohorts.Conclusion To facilitate safe whole liver treatment, it is sometimes necessary to partially or completely occlude main or accessory hepatic arteries. This study shows that the success of flow redistribution strategies can be quantitatively measured, and there is no adverse impact on time to recurrence or overall survival outcomes.
Keywords: embolization, therapeutic; liver neoplasms; microspheres; retrospective studies; survival rate